Analysing students' perceptions of online mathematics learning using the fuzzy conjoint method / Zurina Kasim and Nur Izza Hazwani Azali Azman - Kasim, Zurina; Azali Azman, Nur Izza Hazwani (UiTM Cawangan Perlis, 2023)
Online distance learning is increasingly popular, especially since the pandemic Covid-19. All stages of learning from elementary to university level use online learning. Because of students' various learning abilities, it takes motivation and support from their surroundings to learn new things. It is important to understand students' experiences, perspectives, and preferences toward online distance learning. This study analyzes the perceptions of online mathematics learning among 40 undergraduates who were majoring in mathematics management at the Faculty of Computer and Mathematical Sciences, UiTM Perlis. The perceptions were analyzed in 3 dimensions which are students' opinions, students' performance, and lecturers' roles in online mathematics learning using the fuzzy conjoint method. The degree of Similarity is used to rank each attribute in each dimension. According to the findings, all attributes were rated "neutral" except for one attribute which was rated "strongly disagreed". Students rated "strongly disagreed" that they sometimes copy each other works blindly during the online assessment (students' performance). Students viewed mathematics as a hard subject to learn online even though they had flexible time to study the feedback on tests/quizzes returned by the lecturers (students' opinion). The lecturers played their role well always giving feedback on student assessment and providing detailed instructions on how to participate in online learning (lecturers' role). This study helps teachers as well as the university to understand students' experiences, perspectives, and preferences. Hence, it helps find a way to improve the quality of online education.